Prevalence of Edwardsiella ictaluri in cage cultured Pangasius spp in Pahang River and their risk factors - Nordin, Amira Syahidah; Mansor, Nur Nazifah; Ramly, Rimatulhana; Sabuti, Asnor Azrin; Mohd Ibrahim, Mohamad Shafiq (International Society of Academicians, 2024)
Striped catfish, Pangasianodon hypophthalmus is a native species to most Asian countries, including Malaysia which faced series of bacterial disease such as edwardsiellosis caused by E.ictaluri. Edwardsiella ictaluri is a Gram-negative intracellular bacterial pathogen which had caused mortalities in farmed or wild fish in lots of countries and accountable for large economic losses. This study was conducted to determine disease status of Pangasius spp due to Edwardsiella ictaluri and to determine the risk factors of E.ictaluri in striped catfish in Pahang River, Malaysia. Four sampling sites were chosen, two sites in Pekan (Kampung Belimbing and Kampung Tanjung Pulai) and two sites in Temerloh (Kampung Teluk Ira and Kampung Bintang). Thirty samples were collected from each farm for 6 months consecutively and four organ tissues were taken which were liver, spleen, kidney, and brain. External and internal clinical signs were recorded accordingly. DNA was extracted from all tissues and pursued for PCR to detect the presence of Edwardsiella ictaluri. Results show that the infected fish has gross internal clinical signs such as patchy liver, white nodular spleen, and congested kidney. The prevalence rate of E.ictaluri was highest at Kampung Tanjung Pulai in June with 16.67% compared to all farms. No infection of E.ictaluri shown at Kampung Belimbing during the whole sampling session. Spearman’s rho correlation showed that the prevalence of E.ictaluri has strong correlation with temperature in Kampung Tanjung Pulai (p > 0.05). Meanwhile those bacteria prevalence have strong relationship with ammonia, sulfide and total suspended solid (TSS) with p< 0.05. The susceptible size for this bacterium in striped catfish is between 1 to 50g. To our knowledge, this paper is the first report for Edwardsiella ictaluriin cage cultured P.hypopthalmus in Pahang River, Malaysia.